INTEGRASI DATA GOVERNANCE DAN DATA QUALITY MANAGEMENT DALAM MENINGKATKAN EFISIENSI OPERASIONAL - Annisa Fitri Adina Hutabarat; Muhammad Irwan Padli Nasution (JURNAL ILMIAH NUSANTARA, 2025)
In the era of digital transformation, data has become a strategic asset for organizations in increasing competitiveness and operational efficiency. However, the main challenge faced is how to ensure that the data owned is accurate, consistent, secure, and in accordance with business needs. In this context, the integration between data governance and data quality management is a strategic solution that not only focuses on data governance arrangements, but also ensures high data quality on an ongoing basis. Data governance provides a framework that includes policies, roles, responsibilities, and standards in data management. Meanwhile, data quality management plays a role in identifying, measuring, and improving data quality through a systematic process.This study aims to examine in depth how the integration of the two approaches can have a significant impact on increasing the operational efficiency of the organization. The research method used is a qualitative approach with literature studies and case study analysis of several organizations in the public and private sectors that have implemented data governance and data quality management practices. The results of the study show that the synergy between data governance and data quality management can reduce data duplication, increase the speed of business processes, strengthen data- driven decision making, and improve compliance with regulations. These findings underscore the importance of developing an integrative framework that is adaptive to organizational needs and technological changes.This research provides theoretical and practical contributions to the development of data management strategies in various sectors, as well as being the basis for designing effective and sustainable data governance policies.